2008
DOI: 10.1200/jco.2008.16.1612
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor and Vascular Endothelial Growth Factor Receptor-2 Genetic Polymorphisms With Outcome in a Trial of Paclitaxel Compared With Paclitaxel Plus Bevacizumab in Advanced Breast Cancer: ECOG 2100

Abstract: A B S T R A C T PurposeNo biomarkers have been identified to predict outcome with the use of an antiangiogenesis agent for cancer. Vascular endothelial growth factor (VEGF) genetic variability has been associated with altered risk of breast cancer and variable promoter activity. Therefore, we evaluated the association of VEGF genotype with efficacy and toxicity in E2100, a phase III study comparing paclitaxel versus paclitaxel plus bevacizumab as initial chemotherapy for metastatic breast cancer. Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
413
8
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(452 citation statements)
references
References 50 publications
24
413
8
7
Order By: Relevance
“…For example, there is proving to be considerable genetic variability within the VEGF gene, evidenced by multiple single nucleotide polymorphisms (SNPs). Notably, certain VEGF SNPs were shown to predict tumor responses and overall survival of metastatic breast cancer patients receiving combination of chemo‐ and anti‐VEGF therapy (bevacizumab) (Jain et al., 2009; Schneider et al., 2008). These provocative observations, while lacking mechanistic details, may help explaining the puzzling therapeutic heterogeneity of patient's responses to anti‐VEGF therapy, and call for auditing genetic variation and gene expression signatures in vascular cells.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…For example, there is proving to be considerable genetic variability within the VEGF gene, evidenced by multiple single nucleotide polymorphisms (SNPs). Notably, certain VEGF SNPs were shown to predict tumor responses and overall survival of metastatic breast cancer patients receiving combination of chemo‐ and anti‐VEGF therapy (bevacizumab) (Jain et al., 2009; Schneider et al., 2008). These provocative observations, while lacking mechanistic details, may help explaining the puzzling therapeutic heterogeneity of patient's responses to anti‐VEGF therapy, and call for auditing genetic variation and gene expression signatures in vascular cells.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…La présence de ces facteurs en forte concentration dans le plasma ne permet cependant pas de prédire clairement la réponse aux agents antiangiogéniques. En effet, l'hétérogénéité des tumeurs mais aussi le polymorphisme qui existe pour les gènes codant le VEGF et ses récepteurs, constituent une partie importante de la variabilité observée dans les réponses aux traitements [44]. La complexité liée aux processus de l'angiogenèse tumorale et de la résistance aux agents qui l'inhibent, nécessite de développer des modèles précliniques qui incluent non seulement les données obtenues chez les patients mais également le contexte environnemental représentatif de la tumeur.…”
Section: Les éChanges De Microparticules Et La Présence De Pompes à Eunclassified
“…Unlike other targeted therapies, however, no molecular biomarkers clearly predict bevacizumab efficacy. Recent studies have investigated the influence of VEGF gene polymorphisms (VGPs) on the response to bevacizumab in breast and ovarian cancer (Schneider et al, 2008;Schultheis et al, 2008). Formica et al (2011) first reported a predictive value for PFS of VGPs located in the promoter/5′ UTR in bevacizumab-treated mCRC patients.…”
Section: Molecular Markers Of Vegf Inhibitormentioning
confidence: 99%